OSTEOLOGICAL STUDY ON THE SPERM WHALE PHYSETER MACROCEPHALUS LINNAEUS FROM INDIAN OCEAN - James, P S B R; Soundararajan, R (Indian Journal of Fisheries, 2011)
The skeleton of a miafe sperm will? lie, Physeter macrocephalus Linnaeus (8.1 m) which was stranded on the southern side of Rmisadiai Island" (Gulf of Mannar) on 30th April 1980, is described in detail. The salient features are a trough-shaped asymmertrical skull, long ’V shaped mandible, a vertebral column consisting of seven cervical vertebrae (six of them fused, the first free), eleven thoracic vertebrae with only ten ribs, eight lumbar vertebrae and 23 caudal vertebrae with ten chevron bones attached between 3rd and 4th caudal vertebrae and fairly large forelimbs. Comparison of the skull of this specimen (8.1 m) with that of another male of an estimated length of 17. 4 m did not reveal any essential differences due to age. The osteofagical features in which the present material differs from others on record from elsewhere are mentioned.